2012
DOI: 10.1103/physreve.85.011703
|View full text |Cite
|
Sign up to set email alerts
|

Negative Poisson's ratio and semisoft elasticity of smectic-Cliquid-crystal elastomers

Abstract: Models of smectic-C liquid-crystal elastomers predict that they can display soft elasticity, in which the shape of the elastomer changes at no energy cost. The amplitude of the soft mode and the accompanying shears are dependent on the orientation of the layer normal and the director with respect to the stretch axis. We demonstrate that in some geometries the director is forced to rotate perpendicular to the stretch axis, causing lateral expansion of the sample-a negative Poisson's ratio. Current models do not… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…For elastomers in the smectic-C phase there are several interesting features in the mechanical models, such as spontaneous deformations as observed in nematic elastomers [28,29]. While the set of all deformations that are zero energy (the quasiconvex hull) has been computed [30], the quasiconvex envelope has not, so it is not yet possible to carry out a numerical study as done here for the Sm-A phase.…”
Section: Introductionmentioning
confidence: 99%
“…For elastomers in the smectic-C phase there are several interesting features in the mechanical models, such as spontaneous deformations as observed in nematic elastomers [28,29]. While the set of all deformations that are zero energy (the quasiconvex hull) has been computed [30], the quasiconvex envelope has not, so it is not yet possible to carry out a numerical study as done here for the Sm-A phase.…”
Section: Introductionmentioning
confidence: 99%
“…While in this review we focus on aligned LCEs that undergo a reversible change in order on heating, it should be noted that unaligned, polydomain liquid crystal elastomers exhibit a number of intriguing properties. Extensive research has been carried on polydomain nematic elastomers (PNE) and polydomain smectic elastomers, regarding the polydomain to monodomain transition, the dynamics of relaxation processes, and the reversible actuation of these materials under load. These polydomain LCEs can be designed to retain strain, as such these have the potential to be used as shape memory materials capable of irreversible shape change …”
Section: Introductionmentioning
confidence: 99%
“…A combination of liquid crystal and polymeric network can form a new materialliquid crystal elastomers (LCEs). The special molecular combination endows LCEs with many unique properties such as soft elasticity [Dey et al, 2013;Biggins et al, 2012;Brown and Adams, 2012;Adams and Warner, 2005] and multi-responsiveness [Corbett and Warner, 2009;Finkelmann and Shahinpoor, 2002;Petsch et al, 2014;Xing et al, 2015], which have led to myriad applications ranging from artificial muscle [Finkelmann and Shahinpoor, 2002;Li and Keller, 2006] to stretchable optical devices [Schmidtke et al, 2005;Shilov et al, 1998;Schmidtke et al, 2002;. Recently, several biological materials such as actin filament network [Dalhaimer et al, 2007] and fibrillar collagens [Knight and Vollrath, 2002] have also been found to have similar molecular structure and behaviors as synthesized LCEs.…”
Section: Introductionmentioning
confidence: 99%